Identification and Antibiotic‐Susceptibility Profiling of Infectious Bacterial Agents: A Review of Current and Future Trends. Issue 1 (26th August 2018) - Maugeri, Gaetano; Lychko, Iana; Sobral, Rita; Roque, Ana C. A.
Abstract : Antimicrobial resistance is one of the most worrying threats to humankind with extremely high healthcare costs associated. The current technologies used in clinical microbiology to identify the bacterial agent and profile antimicrobial susceptibility are time‐consuming and frequently expensive. As a result, physicians prescribe empirical antimicrobial therapies. This scenario is often the cause of therapeutic failures, causing higher mortality rates and healthcare costs, as well as the emergence and spread of antibiotic resistant bacteria. As such, new technologies for rapid identification of the pathogen and antimicrobial susceptibility testing are needed. This review summarizes the current technologies, and the promising emerging and future alternatives for the identification and profiling of antimicrobial resistance bacterial agents, which are expected to revolutionize the field of clinical diagnostics. Abstract : The fast identification and profiling of antimicrobial susceptibility in bacterial infections are critical factors to consider for a successful and targeted therapy. Future and emerging technologies are particularly suited to address these challenges, thereby contributing to control the emergence and spread of antibiotic resistant bacteria.